Comprehensive tension setting optimisation technique for a cold rolled strip during continuous annealing. (3rd July 2018) - Wang, R.; Bai, Z. H.; Du, J. C.; Wang, Y. X.; Cui, Y. Y.; Guo, Z. S.; Song, Z. F.
ABSTRACT: The previous tension setting for the continuous annealing process (CAP) is not comprehensive; that is, it does not synthetically consider the factors of strip deviation, buckling, flatness and width narrowing. To address this issue, this study integrated the mechanical and technological characteristics of a continuous annealing line to present a comprehensive control index that can characterise the stability of a travelling strip. Meanwhile, strip deviation, buckling, strip shape and width narrowing were regarded as constraints in each process section. A comprehensive optimisation technique for the tension setting during CAP was then established, and a related theory was applied during production. In addition, a comprehensive tension setting optimisation software was developed for a cold rolled strip during continuous annealing, and the comprehensive optimisation of the tension parameters in each process section was realised. A practical implementation proves that the developed technique exhibits good application effects and considerable application values.